"I have always said that I am not a feminist, but ...": moderate feminism in the narratives of Finnish women journalists who entered the field between 1960 and 1990 - Kurvinen Heidi (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This article studies lived experiences of gender equality and feminism in Finnish newsrooms between 1960 and 1990. On one hand, the journalists I interviewed claimed they had reported on diverse social issues related to gender equality and feminism throughout their careers. On the other hand, they embraced the idea that the journalistic profession had achieved more gender equality in Finland than in other countries in the Global North and the Nordic region. Using narratives collected from 31 women journalists, I use this contradiction to problematise the relationship between experiences of gender equality and the desire to struggle for feminist demands in professional journalism. I do so by adopting the analytical approach of moderate feminism.